Éduquer à la citoyenneté démocratique par l’innovation sociale : l’idéal de l’entrepreneuriat social remis en question - Mailhot, Chantale; Gaudet, Stephanie; Drapeau, Émilie; Fuca, Jose (Canadian Journal of Nonprofit and Social Economy Research, 2021)
The concepts of entrepreneurship and citizenship intersect more and more in the educational projects of social entrepreneurship. In this article, we have analyzed an experiment conducted by a nonprofit organization whose mission is to increase citizen participation. We are interested in the discourses and tools that it has mobilized for training in social entrepreneurship. Our objective is to uncover the norms and values underlying the conception of citizenship transmitted through the training. We show that there are tensions between the aims of democratic citizenship promoted by the organization and the concept of the citizen that underlies training in social entrepreneurship. Our contribution is twofold: 1) We enrich the literature on education for democratic citizenship by analyzing a new approach, that of education in social entrepreneurship; 2) We take a critical look at the concept of social entrepreneurship when it is used in training for democratic citizenship by analyzing this practice and framing it within the field of social innovation
Number: 2
Keywords: Entrepreneuriat social; Innovation sociale